Justification for the Implementation of Citywide GPS System - Jadoon, Adil Khan (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2003)
Over the past few years, there has been an increase in the use of telematics in Demand Responsive Transport like taxis, so as to maximize the ever-increasing demand. To provide better customer service in the competitive taxi business, use of telematics becomes ever more important. In Dublin, National Radio Cabs uses satellite based Global Positioning System to dispatch and monitor its taxi fleet. The research work presented in this thesis looks at the Global Positioning System data provided by National Radio Cabs in terms of customer waiting times, effect on number of dispatches, travel time duration and customer waiting time ratio. The thesis looks at the improvements in these transport variables so as to justify the implementation of Global Positioning system on citywide basis. Average CWT varies between 5-34 minutes as compared to 20-45 minutes. Average travel time is approximately 21 minutes between 6 a.m. and 10 a.m. and average travel time in the evening is 25 minutes berween 3 p.m. and 7 p.m. Average travel time is approximately 22 minutes at any time of the day. Average taxi dispatches are 1411 per day as compared to 700 before using GPS. Average CWT ratio is 0.37.
Keywords: Engineering, Ph.D.; M.Sc. Trinity College Dublin